Analisis Dampak Kebijakan Perdagangan Internasional Terhadap Sektor Ekspor - Rosdiana; Heppi Syofya; Novegya Ratih Primandari; Eva Yuniarti Utami; Nuralam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze the impact of international trade policies on the export sector. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are In international trade there are several policies that include tariffs, export subsidies, import authorities, local content requirements, government controls, and international trade agreements. In addition, there are impacts of international trade policies on the Indonesian export sector including international market access, protecting local industries, new market access, and quality standards.